Production of Gloeophyllum trabeum Endoglucanase Cel12A in Nicotiana benthamiana for Cellulose Degradation - Geem, Kyoung Rok; Song, Younho; Hwang, Inhwan; Bae, Hyeun-Jong; Lee, Dong Wook (Frontiers in Plant Science, 2021)
Lignocellulosic biomass from plants has been used as a biofuel source and the potent acidic endoglucanase GtCel12A has been isolated from Gloeophyllum trabeum, a filamentous fungus. In this study, we established a plant-based platform for the production of active GtCel12A fused to family 3 cellulose-binding module (CBM3). We used the signal sequence of binding immunoglobulin protein (BiP) and the endoplasmic reticulum (ER) retention signal for the accumulation of the produced GtCel12A in the ER. To achieve enhanced enzyme expression, we incorporated the M-domain of the human receptor-type tyrosine-protein phosphatase C into the construct. In addition, to enable the removal of N-terminal domains that are not necessary after protein expression, we further incorporated the cleavage site of Brachypodium distachyon small ubiquitin-like modifier. The GtCel12A-CBM3 fusion protein produced in the leaves of Nicotiana benthamiana exhibited not only high solubility but also efficient endoglucanase activity on the carboxymethyl cellulose substrate as determined by 3,5-dinitrosalicylic acid assay. The endoglucanase activity of GtCel12A-CBM3 was maintained even when immobilized on microcrystalline cellulose beads. Taken together, these results indicate that GtCel12A endoglucanase produced in plants might be used to provide monomeric sugars from lignocellulosic biomass for bioethanol production.